Clinical and Economic Outcomes of Patients Undergoing Guideline-Directed Management of Pancreatic Cysts. (17th October 2020) - Lobo, Jennifer M.; Scheiman, James M.; Zaydfudim, Victor M.; Shami, Vanessa M.; Sauer, Bryan G.
Abstract : INTRODUCTION: Numerous guidelines exist for the management of pancreatic cysts. We sought to compare the guideline-directed management strategies for pancreatic cysts by comparing 2 approaches (2017 International Consensus Guidelines and 2015 American Gastroenterological Association Guidelines) that differ significantly in their thresholds for imaging, surveillance, and surgery. METHODS: We developed a Monte Carlo model to evaluate the outcomes for a cohort of 10, 000 patients managed per each guideline. The primary outcome was mortality related to pancreatic cyst management. Secondary outcomes included all-cause mortality, missed cancers, number of surgeries, number of imaging studies, cumulative cost, and quality-adjusted life years. RESULTS: Deaths because of pancreatic cyst management and quality-adjusted life years were similar in both guidelines at a significantly higher cost of $3.6 million per additional cancer detected in the Consensus Guidelines. Deaths from "unrelated" causes (1, 422) vastly outnumbered deaths related to pancreatic cysts (125). Secondary outcomes included more missed cancers in the American Gastroenterological Association guideline (71 vs 49), more surgeries and imaging studies in the Consensus guideline (711 vs 163; 116, 997 vs 68, 912), and higher cost in the Consensus guideline ($168.3 million vs $89.4 million). As the rate of malignant transformation increases, a more-intensive guideline resulted in fewer deaths related to pancreatic cyst management. DISCUSSION: Our study demonstrates trade-offs between more- and less-intensive management strategies for pancreatic cysts. Although deaths related to pancreatic cyst management were similar in each strategy, fewer missed cancers in the more-intensive surveillance strategy is offset by a greater number of surgical deaths and higher cost. In conclusion, our study identifies that if the rate malignant transformation of pancreatic cysts is low (0.12% annually), a less-intensive guideline will result in similar deaths to a more-intensive guideline at a much lower cost.